A complex ray approach to the acoustics of fluid-loaded structures - Smith, Bridget J. (1995)
This thesis provides a geometrical asymptotic approach to some fluid-loading problems in acoustics.The first half concerns the bulk wave insonification of flat fluid-loaded membranes and elastic solids. Particular attention is paid to the excitation of the leaky surface wave of these configurations, with a new geometrical interpretation, using complex rays, of the displacement of the cut-off angle from the Mach angle given. The types of bulk wave insonification considered are cylindrical and spherical waves and Gaussian beam incidence, and all these fields are described in terms of complex rays.The second half concerns the bulk wave insonification of convex fluid-loaded boundaries. Specifically the impedance and membrane boundaries are considered undergoing plane wave incidence. Unlike the flat boundary problems considered, the plane wave can excite surface waves and this is considered. Finally, the asymptotic field produced when a ray is tangentially incident to a soft convex boundary, thus exciting a creeping wave, is obtained.